Toward Meaning-Making Historical Consciousness: An Analysis Sinnbildung Gen Z - Atief Arezal Fatah; Kurniawati Kurniawati; Budiaman Budiaman (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
Historical awareness is one of the fundamental objectives of history learning because it is closely related to the development of students' skills in interpreting the relationship between the past, present, and future. This study aims to analyse students' historical consciousness, based on Jörn Rüsen's theoretical framework, in response to international conflict phenomena. This study uses a qualitative research model with an instrumental case study design. Data were collected through in-depth interviews using photo elicitation with four 12th-grade high school students from two Muhammadiyah institutions in East Jakarta. The findings will use a data analysis model based on the Values Coding model. The results of the study show that there are three variations of historical awareness: traditional-exemplary, critical-transitional, and genetic. These findings lead to the conclusion that the meaning of history is influenced by experience, values, and individuals, making Rüsen's theory quite relevant as an analytical framework for understanding the development of narratives and orientations in participants' thinking. This study implies the importance of history learning that encourages students' skills in interpreting and reflecting on various historical materials.